Weed Species in the Campina Experimental do Cerrado - Teixeira, Luísa Silva; Grossi Júnior , José Paulo Perozim; Weiser , Veridiana de Lara; Enokibara, Marta (Technical and Scientific Journal Green Cities, 2025)
ABSTRACTObjective – To present the weed species found in the Campina Experimental do Cerrado, with emphasis on the seedling and juvenile stages, highlighting diagnostic morphological traits that enable accurate identification and contribute to the adoption of more effective management practices.  Methodology – A descriptive approach was adopted, based on direct and continuous observation of the spontaneous emergence of plants. Each specimen was individually analyzed and described based on visible morphological traits, such as leaf shape and initial growth structure. For visual standardization, each specimen was photographed in two contexts: in its natural environment and under controlled conditions, against a blue checkered background to support the management and early identification of weed species, distinguishing them from intentionally cultivated plants.  Originality/Relevance – The relevance of this study lies in its focus on the early identification of weed species using standardized visual records, facilitating recognition by non-specialists. Its originality resides in the integration of accessible images and morphological descriptions, bridging technical knowledge and field practice while contributing to appropriate management strategies.  Results – A total of 19 weed species were identified, and visual records and morphological descriptions were produced to differentiate them from similar cultivated species, allowing for quick and efficient recognition during the early stages of development.  Theoretical/Methodological Contributions – The theoretical contributions include advancing the understanding of weed species diversity at early developmental stages, integrating technical knowledge with field-based practice, enabling early identification by non-specialists, and supporting conservation actions that distinguish cultivated species from weeds, in alignment with naturalistic garden management strategies.  Social and Environmental Contributions – Social contributions include empowering non-specialist observers and promoting sustainable practices. Environmentally, the study supports biodiversity conservation and the sustainable management of naturalistic gardens, considering both ecological functionality and landscape aesthetics.
Keywords: Savanna; Gardens; Specimen Handling